Perception on Menstrual Cup among Menstruating Students of Kathmandu University - Kunwar, Sonika; Shah, Suveckshya (Samriddhi Journal of Development Studies, 2023)
Menstruation, a globally prevalent phenomenon, often faces cultural barriers hindering proper hygiene practices, particularly in Nepal. This study investigates the perceptions of menstrual cup users and non-users among menstruating students at Kathmandu University, employing the Theory of Planned Behavior as a framework. Through mixed methods, both quantitative and qualitative data were collected and analyzed. Findings reveal no significant relationship between menstrual cup use and financial factors but a meaningful association with sexual activity status. Additionally, significant differences were observed in attitudes and subjective norms between users and non-users. This study underscores the importance of promoting menstrual cup awareness and addressing cultural barriers to enhance menstrual hygiene practices among menstruating individuals in Nepal.